Liquid crystal tunable metamaterial absorber - Shrekenhamer, David; Chen, Wen-Chen; Padilla, Willie J (Physical review letters, 2013)
We present an experimental demonstration of electronically tunable metamaterial absorbers in the terahertz regime. By incorporation of active liquid crystal into strategic locations within the metamaterial unit cell, we are able to modify the absorption by 30% at 2.62 THz, as well as tune the resonant absorption over 4% in bandwidth. Numerical full-wave simulations match well to experiments and clarify the underlying mechanism, i.e., a simultaneous tuning of both the electric and magnetic response that allows for the preservation of the resonant absorption. These results show that fundamental light interactions of surfaces can be dynamically controlled by all-electronic means and provide a path forward for realization of novel applications.